The Selected Factors Affecting to Health-Preventive Behaviors of Primary Knee Osteoarthritis among Teachers in Nakhon Pathom Province - ตันทพงษ์, อุษา; นิมิตรอานันท์, นงพิมล; รุจนเวช, ศศิธร (Journal of The Royal Thai Army Nurses, 2019)
Knee osteoarthritis is the significant public health problem which affects the elderly’s quality of life. It is necessary to provide early preparation for risk people to prevent and delay disease severity. This survey research was aimed to identify the correlation and influencing predictors among selected factors and health preventive behaviors. The samples consisted of 230 teachers who were working at the primary schools in Nakhon Pathom Province. Data were conducted from June to July, 2017. The research instruments were included the knee osteoarthritis severity assessment and preventive health behaviors questionnaire of knee osteoarthritis. These instruments were validated by experts with the reliability of 0.84 and 0.76 respectively. Data were analyzed by using descriptive statistics, Pearson’s Product-moment correlation coefficients and multiple regression. The results revealed that the disease severity perception was significantly related to preventive health behaviors, age, body weight, worked-year number. (r =.145; r = .247; r = .135; r = .755), age was correlated to male and female, and body mass index. (r = .426; r = .755), and age was associated with worked-year number (r = .838). The selected factors presented that female, body mass index, body weight, and age were significantly predicted preventive health behaviors which can be explained 11% of variance. The researchers suggest that nurses should develop health behavior modification program and focus on the influence of predicting factors to prevent and decelerate knee osteoarthritis severity for late adulthood group.